Smoldering and Flaming of Disc Wood Particles Under External Radiation: Autoignition and Size Effect - Wang, Supan; Ding, Pengfei; Lin, Shaorun; Gong, Junhui; Huang, Xinyan (Frontiers in Mechanical Engineering, 2021)
Wildfire is a global issue that causes severe damage to the society and ecosystem. Wood particles and firebrands are the most common fuels in wildland fire, but the size effect on the flaming and smoldering ignition as well as subsequent burning behavior is still poorly understood. In this work, a well-controlled experiment was performed to investigate smoldering and flaming ignitions of stationary disc-shaped wood particles with different diameters (25-60 mm) and thicknesses (15-25 mm) under varying radiant heat flux. The ignition difficulty, in terms of the minimum heat flux, increases from smoldering ignition to piloted flaming ignition and then to flaming autoignition. The minimum heat flux, ignition temperature, and peak burning flux for flaming autoignition all increase with the sample thickness, while insensitive to the sample diameter. During ignition and burning processes, the disc particle deformed due to the interaction between chemical reactions and thermomechanical stresses, especially for smoldering. The characteristic thickness of the smoldering front on wood is also found to be 10-15 mm. This study sheds light on the size effect on the ignition of wood particles by wildfire radiation and helps understand the interaction between flaming and smoldering wildfires.